2020
DOI: 10.1111/jth.15050
|View full text |Cite
|
Sign up to set email alerts
|

Is the COVID‐19 thrombotic catastrophe complement‐connected?

Abstract: In December 2019, the world was introduced to a new betacoronavirus, referred to as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) for its propensity to cause rapidly progressive lung damage, resulting in high death rates. As fast as the virus spread, it became evident that the novel coronavirus causes a multisystem disease (COVID-19) that may involve multiple organs and has a high risk of thrombosis associated with striking elevations in pro-inflammatory cytokines, D-dimer, and fibrinogen, but w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 104 publications
0
62
0
Order By: Relevance
“…Venous thromboembolism (VTE) very commonly complicates the clinical course of inpatients with COVID-19, despite thromboprophylaxis; the risk appears highest among critically ill inpatients monitored in the intensive care unit (ICU). 15 The incidence of VTE in COVID-19 patients has been reported to occur in ∼10-35%, with autopsies indicating that it may reach nearly 60% 12,16 ; with pulmonary embolism being the most common thrombotic complication. 17 A recent large meta-analysis of 44 studies reporting on acute complications and mortality in 14,866 hospitalized COVID-19 patients indicated that VTE occurred in 15%; however, the authors admit to very low-quality evidence due to high heterogeneity and risk of bias (Table 1).…”
Section: Venous Thromboembolism (Vte)/deep Vein Thrombosis (Dvt)/pulmmentioning
confidence: 99%
See 2 more Smart Citations
“…Venous thromboembolism (VTE) very commonly complicates the clinical course of inpatients with COVID-19, despite thromboprophylaxis; the risk appears highest among critically ill inpatients monitored in the intensive care unit (ICU). 15 The incidence of VTE in COVID-19 patients has been reported to occur in ∼10-35%, with autopsies indicating that it may reach nearly 60% 12,16 ; with pulmonary embolism being the most common thrombotic complication. 17 A recent large meta-analysis of 44 studies reporting on acute complications and mortality in 14,866 hospitalized COVID-19 patients indicated that VTE occurred in 15%; however, the authors admit to very low-quality evidence due to high heterogeneity and risk of bias (Table 1).…”
Section: Venous Thromboembolism (Vte)/deep Vein Thrombosis (Dvt)/pulmmentioning
confidence: 99%
“…Due to the involvement of complement and neutrophils, in addition to platelets and other coagulation and endothelial factors, in the pathogenesis of virus-induced immuno-inflammatory coagulopathy and thrombotic microangiopathy, there is a suggestion that early intervention with anticomplement agents and NET inhibition may be important to limit cell/tissue damage and its attendant thrombosis; however, this remains to be tested. 10,12,13…”
Section: Therapeutic Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysregulated immune response, via establishment of a pro-inflammatory feedback loop, presumably exerts damage to the lung parenchyma [30] and triggers a peculiar hemophagocytic lymphohistiocytosis [31] , which has been extensively demonstrated in severe COVID 19 patients. Endothelial injury, mediated by direct SARS-CoV-2 infection of endothelial cells [32] (in which selenium-dependent GPX1 may play a crucial part by enhancing SARS-CoV-2 virulence [8] ) and the generalized excessive pro-inflammatory state, has been robustly implicated in COVID-19 coagulopathy [33] , via multiple mechanisms including platelet activation [34] , fibrinolysis shutdown [35] , [36] , massive von Willebrand factor release [37] , increased thrombin production [4] , disproportionate complement activation leading to thrombogenesis [38] and Neutrophil Extracellular Traps (NETs) formation [39] . Therefore, impairment in selenocysteine synthesis may contribute to COVID-19 coagulopathy via the dysregulated immune response pathway.…”
Section: Evaluation Of the Hypothesismentioning
confidence: 99%
“…This is clinically present as ARDS or AKI [39]. Both diseases, when fully presented are difficult to control even in the ICU settings [40][41][42][43]. Therefore, many strategies focused on prevention of complement activation are proposed as important aspects of COVID-19 treatment.…”
Section: Complement Activation In Sars-cov-2mentioning
confidence: 99%